2018
DOI: 10.1590/s1980-220x2017016903291
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension management: what is the role of case management?

Abstract: Objective The aim of this study was to determine the effect of case management on hypertension management and on adherence to antihypertensive medication and chronic disease care of patients with hypertension. Method This study was conducted as an experimental and randomized controlled study. The sample of the study consisted of randomly selected patients with hypertension who did not have communication problems, who used antihypertensive medication treatment and whose treatment had been continuing for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 14 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Improvement in blood pressure, BMI, and waist circumference may be associated with improved treatment adherence because the scores in the present study showed significant improvement after 12 months of follow‐up ( p < .001). Zhu et al () and Ozpancar et al () also observed improvements in treatment adherence after an intervention with case management.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Improvement in blood pressure, BMI, and waist circumference may be associated with improved treatment adherence because the scores in the present study showed significant improvement after 12 months of follow‐up ( p < .001). Zhu et al () and Ozpancar et al () also observed improvements in treatment adherence after an intervention with case management.…”
Section: Discussionmentioning
confidence: 91%
“…Ozpancar, Pakyuz, and Topcu () found positive effects of case management on blood pressure in people diagnosed with hypertension: their SBP decreased from 136.16 to 117.5 mmHg ( p < .001) and their DBP decreased from 87.66 to 77.50 mmHg ( p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…The actions were associated with changing healthy lifestyle behaviors (healthy eating, physical activity) and increasing medication adherence. In this sense, the nurse's action in case management is assessed as positive, particularly in relation to people with SAH and especially when it comes to the effect of the guidelines on lifestyle changes and adherence to treatment (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown evidence on the effectiveness of CM developed by nurses for reducing risk factors and decreasing blood pressure levels, as well as improving adherence to the therapeutic regimen. (5)(6)(7)(8)(9) Case management actions also have proved beneficial to increase knowledge about the disease and self-management of treatment. (10) They reduce the number of hospitalizations and aggravations that require emergency care, impacting the improvement of quality of life.…”
Section: Outcomes (Follow Up)mentioning
confidence: 99%